Synthesis of nano emulsion from waste cooking oil for enhanced oil recovery applications. (August 2019) - Noor, M I I M; Islam, A; Saalah, S; Ken, C C; Anisuzzaman, S M; Kamin, Z
Abstract: Enhanced oil recovery (EOR) is a tertiary method to extract potential oil in a matured well. Emulsion, which is one EOR method has properties which enable it to recover oil remains in reservoir rocks of the matured well. Nano sized emulsion or nano emulsion able to recover trapped oil, by capillary force in fine pores of the reservoir rock. Nano emulsion reduces the oil-water interfacial tension and therefore changes the wettability of the reservoir rock. However, the nano emulsion is uneconomical and unstable. Therefore, this work aimed to produce nano emulsions by using low cost waste cooking oil, Tween 80 and Span 80. Ultra-sonication was used to reduce the size of the emulsion. The concentration of surfactant, power of ultra-sonication and time of sonication were varied to study the stability of the oil-in-water and size of the emulsion using the Malvern Zetasizer. The nano emulsion was then tested on a crude oil soak meligan formation sand rock to test the performance of the nano emulsion. The result show values of zeta potential and droplet size were - 15.3 mV and 262.1 d.nm respectively. The emulsion droplet sizes were about 500 nm with milky white appearance. The nano emulsion shows positive results as 63.89 % crude oil displaced from the soaked meligan formation sand rock. As a conclusion, the nano emulsion produced from waste cooking oil can potentially be used for EOR.